Software for prioritizing conservation actions based on probabilistic information. Issue 4 (16th July 2021) - Watts, Matthew; Klein, Carissa J.; Tulloch, Vivitskaia J. D.; Carvalho, Silvia B.; Possingham, Hugh P.
Abstract: Marxan is the most common decision‐support tool used to inform the design of protected‐area systems. The original version of Marxan does not consider risk and uncertainty associated with threatening processes affecting protected areas, including uncertainty about the location and condition of species' populations and habitats now and in the future. We described and examined the functionality of a modified version of Marxan, Marxan with Probability. This software explicitly considers 4 types of uncertainty: probability that a feature exists in a particular place (estimated based on species distribution models or spatially explicit population models); probability that features in a site will be lost in the future due to a threatening process, such as climate change, natural catastrophes, and uncontrolled human interventions; probability that a feature will exist in the future due to natural successional processes, such as a fire or flood; and probability the feature exists but has been degraded by threatening processes, such as overfishing or pollution, and thus cannot contribute to conservation goals. We summarized the results of 5 studies that illustrate how each type of uncertainty can be used to inform protected area design. If there were uncertainty in species or habitat distribution, users could maximize the chance that these features were represented by including uncertainty using Marxan with Probability. Similarly, if threatening processes were considered, users minimized the chance that species or habitats were lost or degraded by using Marxan with Probability. Marxan with Probability opens up substantial new avenues for systematic conservation planning research and application by agencies. Resumen: Marxan es la herramienta de apoyo a las decisiones que más comúnmente se usa para orientar el diseño de los sistemas de áreas protegidas. La versión original de Marxan no considera el riesgo y la incertidumbre asociados con los procesos amenazantes que afectan a las áreas protegidas, incluyendo la incertidumbre sobre la ubicación y la condición de las poblaciones de las especies y su hábitat ahora y en el futuro. Describimos y analizamos la funcionalidad de una versión modificada de Marxan: Marxan con Probabilidad. Este software considera explícitamente cuatro tipos de incertidumbre: probabilidad de que una característica exista en un lugar en particular (estimada con base en los modelos de distribución de especies o con modelos de población espacialmente explícitos); probabilidad de que las características de un sitio se pierdan en el futuro debido a un proceso amenazante, como el cambio climático, las catástrofes naturales y las intervenciones humanas descontroladas; probabilidad de que una característica existirá en el futuro debido a los procesos naturales de sucesión; como los incendios o las inundaciones; y probabilidad de que una característica exista pero haya sido degradada por los procesos amenazantes, como la sobrepesca y la contaminación, y por lo tanto no puede contribuir a los objetivos de conservación. Sintetizamos los resultados de cinco estudios que ilustraron cómo cada tipo de incertidumbre puede usarse para orientar el diseño del área protegida. Si hubiera incertidumbre en la distribución de la especie o de su hábitat, los usuarios podrían maximizar la posibilidad de que estas características estuvieran representadas mediante la inclusión de Marxan con Probabilidad. De manera similar, si los procesos amenazantes estuvieran considerados, los usuarios minimizarían la posibilidad de que se pierda la especie o degrade el hábitat usando Marxan con Probabilidad. Marxan con Probabilidad abre nuevas vías importantes para la investigación sobre la planeación sistemática de la conservación y su aplicación por parte de las agencias. 【摘要】: Marxan 软件是指导保护区系统设计的常用决策支持工具。然而, Marxan 的原始版本没有考虑到影响保护区的威胁过程的风险和不确定性, 包括物种种群和栖息地现在及未来位置和各种条件的不确定性。我们设计并检验了改进版 Marxan 软件的功能, 即考虑可能性的 Marxan (Marxan with Probability) 。该软件明确地考虑了四种不确定性:一种特征存在于特定地点的可能性 (基于物种分布模型或空间显式种群模型估计); 一个位点的特征由于未来气候变化、自然灾害, 或不受控制的人类干预等威胁过程而消失的可能性;一种特征由于自然的连续过程, 如火灾或洪水, 在未来存在的可能性;特征虽然存在, 但由于过度捕捞或污染等威胁过程而退化, 因此不能促进保护目标实现的可能性。我们总结了五项研究的结果, 来说明每种类型的不确定性如何用于指导保护区设计。如果物种或栖息地分布存在不确定性, 用户可以通过使用 Marxan with Probability 来纳入不确定性, 从而尽可能地表示出这些特征。类似地, 如果要考虑威胁过程, 用户也可以使用 Marxan with Probability 将物种或栖息地丧失或退化的可能性降至最低。 Marxan with Probability 这一软件为各机构的系统保护规划研究和应用开辟了重要新途径。【翻译: 胡怡思; 审校: 聂永刚】